Tenkostěnný pravoúhlý přeliv bez bočního zúžení ovlivněný šířkou koryta - Zmítko, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Diplomová práce řeší, propagaci šířky přelivu (koryta) na kapacitu přelivu. Míra ovlivnění je analyzována laboratorním měřením na modelech s šířkou přelivu (koryta) od 0,02 m po šířku 0,50 m. Jsou analyzovány různé přepadové výšky a průtoky, při kterých je počítán součinitel přepadu. Výsledky jsou porovnány s předchozími pracemi, především pak s prací Kindsvatera a Cartera (1957) a Schodera a Turnera (1929), kdy jsou použity stejné postupy k výpočtu součinitele přepadu. Práce obsahuje teoretické uvedení do problému tenkostěnných přelivů a otázky vzniku mezní vrstvy při proudění kapaliny, navazuje analytická část. V analytické části jsou publikovány výsledky měření, jejich porovnání a zhodnocení. Práce je zakončena zhodnocením a doporučením.

The diploma thesis deals with the propagation of a weir (channel) width on the weir capacity. The influence rate is analyzed by laboratory measurements on models with a weir (channel) width of 0,02 m to a width of 0,50 m. Different heads are analyzed and different discharges that calculate the discharge coefficient. The results are compared with previous works, especially with the work of Kindsvater and Carter (1957) and of Schoder and Turner (1929), where the same procedures are used to calculate discharge coefficients. The thesis contains a theoretical introduction to the problem of thin-plate weirs and the problem of the formation of the boundary layer in the flow of liquid, following with the analytical part. In the analytical part, the results of measurements, their comparison, and evaluation are published. The work is completed with evaluation and recommendations.
Full-width thin-plate rectangular weir influenced by channel width
Keywords: Tenkostěnný přeliv; mezní vrstva; přepadový paprsek; šířka koryta; měření průtoku; přepadový součinitel; Thin-plate weir; boundary layer; overflow nappe; channel width; flow measurement; discharge coefficient